Time to diagnosis in esophageal cancer: a cohort study. (2nd September 2018) - Cavallin, Francesco; Scarpa, Marco; Cagol, Matteo; Alfieri, Rita; Ruol, Alberto; Chiarion Sileni, Vanna; Rugge, Massimo; Ancona, Ermanno; Castoro, Carlo
Abstract: Background: The association between shorter time to diagnosis and favorable outcome is still unproven in esophageal cancer. This study aims to evaluate the effect of time to diagnosis on patient prognosis. Material and methods: Retrospective cohort study of all 3613 symptomatic patients referred for esophageal cancer to our center from 1980 to 2011. Time to diagnosis was calculated as the number of days from first symptom onset to the diagnosis of esophageal cancer. The main outcome measures were: resectability and severe malnutrition at diagnosis; postoperative morbidity, mortality and survival. Results: Longer time to diagnosis was significantly associated with severe malnutrition at diagnosis (odds ratio (OR): 1.003, 95% confidence interval (C.I.).: 1.001–1.006) but not with resectability (OR: 0.997, 95% C.I.: 0.994–1.001). Longer time to diagnosis was not associated with postoperative morbidity (OR: 1.000, 95% C.I.: 0.998–1.003), postoperative mortality (OR: 1.002, 95% C.I.: 0.998–1.006), five-year overall survival (hazard ratio (HR): 0.999, 95% C.I.: 0.997–1.001) or five-year disease free survival (HR: 0.999, 95% C.I.: 0.998–1.001). Conclusion: Longer time to diagnosis did not affect resectability, postoperative morbidity or survival. Further campaigns to raise awareness of cancer among population and primary health care providers may have limited effect on clinical outcome.